Remarkable LnIII3FeIII2 clusters with magnetocaloric effect and slow magnetic relaxation. Issue 2 (12th November 2014) - Li, Han; Shi, Wei; Niu, Zheng; Zhou, Jing-Min; Xiong, Gang; Li, Lei-Lei; Cheng, Peng
Abstract : Two 3d–4f clusters were reported: Gd3 Fe2 possesses significant magnetic entropy change and slow magnetic relaxation is observed in Dy3 Fe2 . Abstract : Two remarkable pentanuclear 3d–4f clusters of Ln3 Fe2 were synthesized and structurally characterized. Magnetic studies indicate that Gd3 Fe2 possesses the significant magnetic entropy change (−Δ S m ) of 31.7 J kg −1 K −1 and slow magnetic relaxation is observed in the anisotropic Dy-analogue.